Impact the Implementation of Feto-Maternaltriage Program Upon Maternal Health Outcomes in Maternity Hospitals of Baghdad City - Wisam M. Muttaleb (Pakistan Journal of Medical & Health Sciences, 2022)
Triage is a major portion of clinical hazard administration in all divisions when clinical load surpasses clinical accessibility. (Jones,K 2006). Triage is used to sort, to direct requires clinical judgments and to rapidly assess a patient and assign a priority based on clinical need. Also triage considers as a fundamental cornerstone of clinical risk management (Mackway-Jones,k 2006). triage in obstetric area become one of the latest obstetric services to emerge.( PA-PSRS 2015 ). "In the last years, OB triage become important in the OB services in most hospitals in the world and developed a triage area adjacent to the labor and delivery department (The Pennsylvania Patient Safety Advisory 2008). According to triage protocol the women should be treated according to the severity or the acuity of the case and not the time of her arrival to the outpatient clinic.